Discussing School Socioeconomic Segregation in Territorial Terms: The Differentiated Influence of Urban Fragmentation and Daily Mobility [Discutir la Segregación Socioeconómica Escolar en Términos Territoriales. la Influencia Diferenciada de la Fragmentación Urbana y la Movilidad Cotidiana] - Cordoba-Calquin, C (Instituto de Geografia, 2017)
Chile is one of the OECD countries with higher levels of socioeconomic segregation in its educational system. This may be explained by the incidence of institutional factors (fees and school selection processes), sociocultural factors (families’ appraisals and behaviors towards school choice) and contextual factors, among which residential segregation would stand as the most relevant. This article analyzes the relation between school location, students’ socioeconomic status and student s place of origin (mobility). The data used was gathered from 1613 surveys responded by primary students’ families. The results evidence that residential segregation only partially influences educational socioeconomic segregation, since the capacity of mobility is a key factor to “break” the association between both phenomena. Therefore, residential segregation would affect to a greater extent low socioeconomic status students who attend schools near their homes and travel distances shorter than children from higher socioeconomic status, who tend to cover longer distances between home and school. Nevertheless, the comparative analysis of the cases complicates drawing conclusions, because students of equal socioeconomic status travel very different distances. The characteristics of the territories where schools are located shed some light on the cause of these differences. From these results, we propose re-discussing the use of the residential segregation concept for explaining phenomena like school segregation, due to the complex interrelations between both territorial fragmentation and urban mobility. © 2017 Universidad Nacional Autonóma de México